Hubungan Penguasaan Pengetahuan Gizi, Frekuensi Konsumsi Susu Rendah Lemak dengan Status Gizi Atlet Futsal Klub Bluemosphere Kabupaten Jombang - Aliyah, Laily Ni'matul; Sulandjari, Siti (Jurnal Gizi dan Kesehatan Nusantara, 2021)
An important aspect of supporting athlete performance is having a good nutritional status. Many factors can affect the nutritional status of athletes, including having good nutritional knowledge, adequate intake of macro and micro nutrients. One of the macro nutrients found in low-fat milk, not only supports nutritional status but can be used as an alternative drink for athletes before training or competition. The goal of this study is to see if there is a link between nutritional knowledge and athletes nutritional status, as well as if there is a link between the frequency of low-fat milk consumption and athletes nutritional health. This is a non-experimental study employing a quantitative methodology. The research subjects were 30 futsal athletes at the Bluemosphere Club, Jombang Regency, aged 19-20 years. The independent variables include nutritional knowledge and frequency of consumption of low-fat milk. The dependent variable includes nutritional status. Statistical test analysis used is Spearman rank correlation. The findings of the data analysis revealed a link between nutritional knowledge and nutritional status, the significance value was 0.011 and the Correlation Coefficient was 0.457 in a positive direction. There is no relationship between the frequency of consumption of low-fat milk with nutritional status, the significance value is 0.876 and the Correlation Coefficient is 0.030 in a positive direction. Based on the results of the analysis, It was discovered that there was a link between nutritional awareness and nutritional status, but that there was no link between the frequency of low-fat milk consumption and athletes nutritional health.